Relevant aesthetic choices for dysphoric times in contemporary Brazil - Moreira, Paulo (Revista Videre, 2021)
This paper analyzes two films, the fiction feature Bacurau by Juliano Dornelles and Kleber Mendonça Filho and the documentary Democracia em Vertigem by Petra Costa, as well as two essays (“Suspeito que estamos” and “Gente frouxa”) by Nuno Ramos. These are examples of successful cultural productions articulating a clear critical voice with a high level of aesthetic quality and being recognized as meaningful in Brazil and abroad. I want to understand new aesthetic directions that have affected contemporary cultural production in Brazil during the Bolsonaro years. These new directions indicate changes in the choice of narrative genre as well as the use of rhetoric strategies in order to articulate effective voices of resistance in a country dominated by the far right.